2022
DOI: 10.1080/15440478.2022.2070328
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Cotton and cotton/elastane Single Jersey Knitted Fabrics before and after Softening and in Situ Synthesis of Cu-based Nanoparticles

Abstract: The quality of cotton and cotton/elastane single jersey knitted fabrics before and after softening was evaluated through their mechanical properties, pilling, and volume electrical resistivity. Elastane-containing fabrics have higher bursting elongation and stiffness, lower bursting strength, the same or higher pilling grade, and 23-27% lower electrical resistivities compared to 100% cotton due to the increased compactness that enables better contact between the loops, and easier flow of charge through them. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…As a result of the above-mentioned, the loop deformation decreased and fabrics provide greater resistance to bending force contributing to higher stiffness. Ivanovska et al 10 observed the same phenomenon when 1.5% of elastane was introduced; bleached cotton/elastane knitted fabric was found stiffer than 100% cotton fabric (0.680 vs 0.632 N). Based on the performed investigations, Salopek et al 26 concluded that by increasing the elastane content from 5% up to 8%, the bending rigidity of the cotton/elastane knitted fabrics increased due to the higher horizontal and vertical stitch density.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…As a result of the above-mentioned, the loop deformation decreased and fabrics provide greater resistance to bending force contributing to higher stiffness. Ivanovska et al 10 observed the same phenomenon when 1.5% of elastane was introduced; bleached cotton/elastane knitted fabric was found stiffer than 100% cotton fabric (0.680 vs 0.632 N). Based on the performed investigations, Salopek et al 26 concluded that by increasing the elastane content from 5% up to 8%, the bending rigidity of the cotton/elastane knitted fabrics increased due to the higher horizontal and vertical stitch density.…”
Section: Resultsmentioning
confidence: 74%
“…All of the mentioned properties contribute to the knitted fabric quality and are governed by yarn chemical composition and type, applied bleaching, dyeing, and finishing treatments. 10 Cotton, as the most abundant natural cellulose fiber and dominantly used in the textile industry, 11 is usually blended with elastane. Concerning this blend, on one hand, cotton is soft, durable, breathable, easy to care, comfortable, and biodegradable, while on the other hand, elastane is known for its higher stretchability and very good stretch recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Having in mind the total antioxidant and flavonoid contents (2.81 g GAE/100 g d.w., and 0.67 g RE/100 g d.w., respectively) in the orange peel extract, its IC 50 of 65.5 µg/mL, and the fact that oxidative stress along with the different microorganisms negatively affects people’s lives [ 44 ], WO, PA, and CA fabrics dyed at 55, 35 and 25 °C were evaluated for their multifunctionality. Namely, fabric antioxidant activity ( Figure 7 ) was assessed according to the commonly used ABTS method, while their antibacterial activity was tested against two microbial strains, i.e., E. coli , and S. aureus , Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…This direct interaction may in turn inactivate that specific group of AuNPs, which will result in a more pronounced uneven activity. The treated fabrics presented log reductions between 0.50 and 2 [52] or 4 [53], for…”
Section: Discussionmentioning
confidence: 99%